An exploratory study on the influence of socio-demographic characteristics on water end uses inside buildings - Matos, Cristina (2014)
Any strategy of water demand management needs the collaboration of the population involved and so it is important to know how characteristics as residence area, number of residents, presence/absence of children/elders, income level, and educational level, among others, may influence the use of water. Empirical studies that quantify relationship between socio-demographic factors and the water end use patterns inside buildings are still largely lacking. To help to fill this gap this paper gathers information about the characterization of water end use per domestic device in three regions of north of Portugal with different socio-demographic characteristics. The main research goal was to establish indoor water end use patterns per domestic device and to evaluate possible relations between these patterns with the socio-demographic characteristics of the area where the household is, namely the number of residents, the presence/absence of children/elders, the income level and educational level. The washbasin is in average the domestic device with more number of uses in a day (responsible for 34% of the total use), close followed by the kitchen sink (32%), the toilet flush (23%), the bathtub (6%) and finally the dishwasher (3%) and the washing machine (2%). The results found might reflect differences in rural and urban lifestyles once that, with the exception of the kitchen sink, Valpaços is the city that registers the lowest number of uses in the appliances monitored. Significant correlations were found in the following cases: between the residence area and the number of uses in washbasin and in the toilet flush; between the presence of children in the household and the use in the dishwasher; between the income level and the number of uses in the washbasin, in the bathtub, in the washing machine and in the dishwasher.